(untitled) (Acta Scientiarum. Biological Sciences, 2020)
Few studies try to explain the effects in tropical lotic ecosystems of an increase in water temperature on the shredding activity of invertebrate shredders, particularly in association with the quality of the leaf litter and the degree of litter conditioning. Therefore, the aims of this study were as follows: i) to better understand how this key invertebrate shredder group affects the decomposition of different species of leaf litter under gradual increases in temperature and microbial conditioning; and ii) to verify the possible consequences on leaf mass loss (LML). Three species of leaf litter were used in two experiments. In experiment I, the litters of three species (Protium spruceanum, Richeria grandis and Inga laurina) at three conditioning levels (1, 7, 14 days) were tested under five different temperatures (20, 22, 24, 26 and 28°C). In experiment II, the leaf litters of three species were used, without conditioning, under four temperatures (20, 22, 26 and 27°C). The shredding performed by Phylloicus sp. was largely dependent on the lignin and cellulose concentrations in each leaf species, independent of conditioning. The presence or absence of conditioning may cause the shredders to use different energy compensation strategies in response to the temperature increases.